The Learning Strategy of the Uṡmani Method in Improving the Accuracy of Makhārij al-Ḥurūf among Islamic Students at TPQ Al-Basyir Karangsuko - Mufidatur Rofia; Abdul Aziz; Sudirman (Institut Agama Islam Negeri Pontianak, 2026)
Accurate pronunciation of makhārij al-ḥurūf is fundamental to Qur'anic learning, yet instructional strategies employing the Uṡmani Method for this specific purpose remain understudied. This study analyzed the implementation of the Uṡmani Method, its supporting factors, and evaluation practices in improving students' makhārij al-ḥurūf accuracy at TPQ Al-Basyir Karangsuko Pagelaran Malang. A qualitative case study design was applied, with data collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing with source and methodological triangulation. Findings revealed that the Uṡmani Method was implemented systematically through talaqqi, musyāfahah, repetitive drilling on difficult letters, ability-based grouping, and continuous evaluation. Its effectiveness was supported by teacher competence, a gradual jilid-based learning system, a conducive religious environment, and active parental involvement. Evaluation was conducted through daily recitation submissions, jilid promotion assessments, and report card distribution as a medium of communication with parents. Collectively, these strategies improved students' recitation accuracy, self-confidence, and love for the Qur'an.